If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4 = 44 + -2x Reorder the terms: 4 + 3x = 44 + -2x Solving 4 + 3x = 44 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 4 + 3x + 2x = 44 + -2x + 2x Combine like terms: 3x + 2x = 5x 4 + 5x = 44 + -2x + 2x Combine like terms: -2x + 2x = 0 4 + 5x = 44 + 0 4 + 5x = 44 Add '-4' to each side of the equation. 4 + -4 + 5x = 44 + -4 Combine like terms: 4 + -4 = 0 0 + 5x = 44 + -4 5x = 44 + -4 Combine like terms: 44 + -4 = 40 5x = 40 Divide each side by '5'. x = 8 Simplifying x = 8
| 2h-h+5=19 | | 6x^3-36x^2-16x+3=0 | | -7a-3=-4a+7 | | 2x+3.3=8.1 | | 3(x+1)+2x=-2x-4(2x+3) | | 13=-7+6x | | x+5/8=(x/4)+(5/12) | | -2=-2(c-9) | | 14b^2c^3+21bc^5= | | (b-5)+b=43 | | 2x+18=38-3x | | 0=15-3-7x | | 2.11x+100=4.4521+10x | | 4x^2-25x+20=-8x+5 | | (3x-1)(x^2+5x-4)= | | 5h+2h=14 | | 27k-32=-32 | | 14=-7+6x | | 7x=2(x+3) | | (4/7)x-3+(4/5)=(1/5)(x+1) | | 15*.50=x+25+.25 | | 2x+12=28-2x | | (x-3:85-9)6+14=20 | | 4(x+3)+2=405(x+1) | | 7x-11x=56 | | g*8+20=76 | | 63=-3(7-2n) | | -2x^2+y=1 | | 8c+3=10-4c | | (2/5)x-(2/7)+(9/7)x+(1/5)=1 | | 4x=-88 | | -9x+2x+3=-3x |